COMPARISON OF 3 TECHNIQUES FOR ESTIMATING PERIPHYTON ABUNDANCE IN BEDROCK STREAMS - Necchi, O.; Branco, LHZ; Branco, CCZ (E Schweizerbart'sche Verlags, 1995)
Three procedures (line transect, point intercept and quadrat) for estimating abundance of macroscopic components of periphyton (macroalgae and bryophytes) were compared in two bedrock streams from southeastern Brazil on the basis of frequency and percent cover. In addition, two quadrat sizes (25 and 50 cm) were tested for best size. Samplings were all made within a 10 m length stream reach. Differences were tested by means of analysis of variance, ANOVA - one way, Student's t test and Chi-square test, whereas associations among them were evaluated by Pearson's r correlation coefficient. Values of frequency and percent cover varied among the different techniques and periphyton species in both sites but ANOVA, t and Chi-square tests revealed no significant difference (p<0.05) for percent cover in the two sites. No consistent pattern was observed for the different procedures between sites. Values for quadrat (25 and 50 cm) percent cover were positively correlated among distinct periphyton species. Significant differences for frequency were found in only one site. Quadrats of 50 cm produced the highest frequency values, whereas point intercept the lowest in both sites. In terms of spatial variation within the stream segment, significant differences were generally observed among all procedures, except between quadrats. As a rule, highly significant correlations for percent cover were found among the different techniques along the stream reach. The strongest relationships were found for quadrats with the other procedures, whereas the weakest between Line and point. Pros and cons of the three techniques are fully discussed.